Meanings attributed by health professionals to the aging process of institutionalized elderly people - Camila Aparecida Pinheiro Landim Almeida; Francisco Nayran de Oliveira Silva; Vânia Angélica de Sousa e Souza; Verlene de Oliveira Santos; Eliana Campêlo Lago; Wanderson Carneiro Moreira (Rev Rene)
Objective: to analyze the meanings attributed by health professionals to the process of aging of institutionalized elderly. Methods: qualitative study carried out with ten health professionals in two long stay institutions for the elderly. A semistructured interview script was used with questions related to the aging process of institutionalized elderly. The data were analyzed according to the symbol, referent and thought proposed by the Representational Theory of Meaning. Results: the meanings obtained resulted in aspects related to being an elderly; fragile elderly; social exclusion and cultural values (symbol); elements related to the aging process (referent); and the recognition of institutional aspects (thought). Conclusion: the meanings attributed by health professionals to the aging process were related to the fragility of being elderly, in view of social exclusion, cultural aspects and institutionalization. These meanings allow us to reflect on the daily practice of integrality in the care of institutionalized elderly.